Effect of varieties and nutrient management on quality and zinc biofortification of wheat (Triticum aestivum) - ARIF, MOHD; DASHORA, L N; CHOUDHARY, J; KADAM, S S; MOHSIN, MOHAMMED (The Indian Journal of Agricultural Sciences, 2019)
Field experiments were conducted during winter (rabi) season of 2016–17 and 2017–18 at Udaipur (Rajasthan) to study the effect of wheat varieties and nutrient management on zinc biofortification. The treatments consist of four wheat varieties, viz. Raj 4120, Raj 4037, Raj 4079 and Raj 4238 in main plots and seven nutrient management treatments viz. 100% RDN, 100% RDN + ZnSO4 25 kg/ha soil application, 100% RDN + ZnSO4 0.5% foliar spray, 100% RDN + ZnSO4 25 kg/ha soil application + ZnSO4 0.5% foliar spray, 125% RDN + ZnSO4 25 kg/ha soil application, 125% RDN + ZnSO4 0.5% foliar spray and 125% RDN + ZnSO4 25 kg/ha soil application + ZnSO4 0.5% foliar spray in sub plots. The study of different wheat varieties indicated that highest values of yield viz. grain (5707 kg/ha) and straw (8869 kg/ha) yield; quality parameters viz. protein content (12.96%), hectoliter weight (80.48 kg/ hl) and sedimentation volume (45.20 CC); and nutrient content and uptakes of nitrogen, phosphorus, potassium and zinc in both grain and straw was recorded with variety Raj 4037 (on pooled basis). Further, application of treatment 125% RDN + ZnSO4 25 kg/ha soil application + ZnSO4 0.5% foliar spray recorded significantly higher grain (5681 kg/ha) and straw (8265 kg/ha) yield; protein content (13.77%), grain appearance score (7.87), hectoliter weight (80.98 kg/hl), sedimentation volume (46.97 CC) and beta carotene content (3.64 ppm); and nutrient content and uptakes of nitrogen, potassium and zinc in both grain and straw (on pooled basis).